MENELAAH KEMBALI KETENTUAN USIA MINIMAL KAWIN DI INDONESIA MELALUI PERSPEKTIF HERMENEUTIKA - Ahmad Masfuful Fuad (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
Reviewing the minimum marrying age provision through legal hermeneutic approach could analyze three main points: First, the context of the determination of the minimum age to marry in UU No. 1 1974; Second, the authentic meaning of the provisions of the minimum marriage age limit in the UU No. 1 1974; Third, the relevance of the provisions of the minimum marriage age limits and the contribution to the social development of society. The findings of this article are: (1) The context of the birth of Article 7 (1) of UU No. 1 1974 about marriage is the fusion of the social, political, cultural, economic and religious factors; (2) The meaning of the delimitation of the minimum age at marriage in the Marriage Act is to create quality family through preventive cultural practices of early marriage/underage, so that people can realize the goal of marriage is good with no end in divorce and got a good offspring and healthy; (3) The determination of a minimum marriage age limit in Article 7 paragraph (1) is considered to be irrelevant because that is not in accordance with the spirit of the law of the birth of the chapter. Therefore, the necessary review and change the contents of that article in order to contribute to the social development of society, namely in terms of health, education, economy and population.